From magma to macrophage: the grand challenges of volcanic environments - Catherine A. Mériaux; Edward Ntim Gasu; Guillaume Nyagatare; Vicky Ruganzu; Philbert Ntivuguruzwa; Mwumvaneza Mutagoma; Atalay Ayele; Julyan H. E. Cartwright; Valérie Cayol; Laurent Charlet; Claudia Corradino; Antonio Costa; et al. (Bulletin of Volcanology, 2026)
The interdisciplinary study of volcanic processes, which extend across all timescales and lengths, requires a multitude of approaches, ranging from analogue and numerical modelling to observations and fieldwork and extending to mathematics. A conference was held at the East African Institute for Fundamental Research, affiliated with the University of Rwanda, a country which, along with the Democratic Republic of Congo, presents a unique geodynamic context. Located along the East African Rift, an active seismic region, Rwanda is close to two of Africa's most active volcanoes, including Nyiragongo, which overlooks Lake Kivu, a deep volcanic lake rich in dissolved carbon dioxide and methane, the latter of which is used for electricity generation. In this context, the conference addressed many “classic” volcanological topics and their modern advances, such as multiphase lava flows, subsurface magma propagation, seismic and deformation signals from a volcano, modelling of volcanic emission dispersion, and volcanic lakes. Yet, it broadened the discussion to the volcanic particle-water interface and its impact on soils, volcanoes and climate change, and volcanoes and health. This article aims to highlight and share the richness of the integration and interconnectedness of the various questions related to a volcanic environment, as well as their impact on society. Ultimately, this conference also demonstrated the importance of promoting science in Africa and developing countries so that the next generation of African researchers is equipped to address the challenges facing their nations.

Multi-trophic paralytic shellfish toxin risk and management across seafood sectors in Tasmania - Alison Turnbull; Steven Rust; Deborah Bermudes; Andreas Seger (Harmful Algae, 2025)

New insights into gas-driven phase segregation in andesitic enclaves from Mt. Mazama (Crater Lake), USA - Julie Oppenheimer; Katharine V. Cashman; Alison C. Rust; Charles R. Bacon; Amanda Lindoo; Katherine J. Dobson (Bulletin of Volcanology, 2025)
A key process in active magmatic systems is the “recharge” of deep-sourced mafic magma into cooler, more evolved, and crystal-rich shallow reservoirs; recharge may be the cause of, or response to, eruptive activity. Although compositional evidence for recharge has been extensively documented, physical models of recharge are limited, particularly processes that separate exsolving volatiles and melts from rapidly growing crystals. To improve constraints on phase separation behaviors, we re-examine andesitic enclaves in silicic andesite lava flows of Mt. Mazama (Crater Lake), USA, that provided early evidence of gas-driven filter pressing (Bacon, 1986). 2D and 3D imaging shows that enclaves have a sample-spanning crystal framework that is disrupted by melt patches, indicating that initially deformable crystal networks were subject to early phase reorganization. Small enclaves are poorly vesicular and require early gas loss. Large enclaves have porous cores with angular (diktytaxitic) voids that are well-connected in 3D and denser rinds with isolated pores. Large enclave rinds have similar bulk compositions to small enclaves but their less evolved cores require ~ 20% melt removal. In the large enclave, diktytaxitic core textures and gas fingering structures at the core–rind boundary suggest relatively slow late-stage outward gas migration. Both scaling arguments and evidence of outward gas/melt migration require a resistant rind. Rind formation is best explained by differential cooling and demonstrates the importance of thermal gradients for gas-driven filter pressing. A corollary is a limited time scale of recharge, enclave formation, and vesiculation to produce diktytaxitic textures, suggesting that recharge was (near) synchronous with eruption.

Fracturing around magma reservoirs can explain variations in surface uplift rates even at constant volumetric flux - Juliet Biggs; Timothy Rafferty; Jonathan Macha; Edna W. Dualeh; Gregor Weber; Alain Burgisser; Finbar Carroll; Lauren Hart; Alison C. Rust; Mark Gilbertson; Alexandra Morand (Journal of Volcanology and Geothermal Research, 2024)

Magma fragmentation: a perspective on emerging topics and future directions - Thomas J. Jones; Katharine V. Cashman; Emma J. Liu; Alison C. Rust; Bettina Scheu (Bulletin of Volcanology, 2022)
The breaking apart of magma into fragments is intimately related to the eruptive style and thus the nature and footprint of volcanic hazards. The size and shape distributions of the fragments, in turn, affect the efficiency of heat transfer within pyroclastic plumes and currents and the settling velocity, and so the residence time, of particles in the atmosphere. Fundamental work relating the glass transition to the fragmentation of magmas remains at the heart of conceptual and numerical models of volcanic eruptions. Current fragmentation criteria, however, do not predict the sizes and shapes of the resulting fragments, or fully account for the multiphase nature of magmas or ways in which magma can break in a fluidal manner or by thermal stress. The pulsatory, non-steady state nature of some eruptions, and related interactions with these fragmentation criteria, also requires further investigation. Here, we briefly review some recent advances in the field of magma fragmentation and provide a perspective on how integrated field, experimental and numerical modelling studies can address key outstanding challenges.

Sources of uncertainty in the Mazama isopachs and the implications for interpreting distal tephra deposits from large magnitude eruptions - Hannah M. Buckland; Katharine V. Cashman; Samantha L. Engwell; Alison C. Rust (Bulletin of Volcanology, 2020)
Estimating the area of tephra fallout and volume of large magnitude eruptions is fundamental to interpretations of the hazards posed by eruptions of this scale. This study uses the tephra from the caldera forming eruption of Mount Mazama (Crater Lake, OR, USA) to demonstrate the challenges faced when working with large prehistoric tephra deposits and outlines the methodologies required to determine eruption volume and magnitude. We combine > 250 Mazama tephra occurrences, reported by a range of disciplines (including archaeology, paleoclimatology and volcanology), with new field studies to better understand the extent of the distal tephra. We find that the Mazama tephra has been remobilised to varying degrees over the past 7000 years, so each tephra locality was appraised for the likelihood that it records primary tephra fallout. We designated 45 of the distal (> 100 km from source) tephra sites as suitable for use in the production of isopachs using a spline fitting method. The new distal isopachs were then integrated with proximal fallout data and estimates of the ignimbrite volume from previous studies to revise the estimated bulk erupted volume from the climactic Mazama eruption to ~ 176 km 3 (~ 61 km 3 dense-rock equivalent; DRE). This study demonstrates the importance of collating tephra localities from a range of disciplines and that even remobilised deposits provide valuable information about the extent of the deposit. Interpreting remobilised deposits can provide insight into post-eruptive processes that could potentially pose secondary hazards following large magnitude eruptions. We also show that in some circumstances, remobilised deposits preserve important physical properties such as grain size.

Far‐travelled ash in past and future eruptions: combining tephrochronology with volcanic studies - Katharine V. Cashman; Alison C. Rust (Journal of Quaternary Science, 2020)
Studies of recent eruptions have improved our understanding of volcanic ash transport and deposition, but have also raised important questions about the behaviour of far‐travelled (distal) volcanic ash. In particular, it is difficult to reconcile estimates of distal ash mass and transport distance determined from eyewitness accounts, mapped deposits, satellite‐based observations and cryptotephra records. Here we address this problem using data from well‐characterized eruptions that, collectively, include all four data types. Data from recent eruptions allow us to relate eyewitness accounts to mapped deposits on the ground and satellite‐based observations of ash in the air; observations from an historical eruption link eyewitness accounts to cryptotephra deposits. Together these examples show that (i) 10–20% of the erupted mass is typically deposited outside the mapped limits; (ii) estimates of the ash mass transported in volcanic clouds cannot account for all of this unmapped ash; and (iii) ash fall observed at distances beyond mapped deposits can have measurable impacts, and can form cryptotephra deposits with high (>~1000 cm −3 ) shard counts. We conclude that cryptotephra data can be incorporated into volcanological studies of ash transport and deposition and provide important insight into both the behaviour and impacts of far‐travelled volcanic ash particles.

The importance of grain size and shape in controlling the dispersion of the Vedde cryptotephra - Jennifer Saxby; Alison Rust; Katharine Cashman; Frances Beckett (Journal of Quaternary Science, 2020)
Volcanic ash is dispersed in the atmosphere according to meteorology and particle properties, including size and shape. However, the multiple definitions of size and shape for non‐spherical particles affect our ability to use physical particle properties to understand tephra transport. Moreover, although particles are often excluded from operational ash dispersion model setups, ash in tephra deposits 1000 km from source can exceed . Here we measure the shape and size of samples of Vedde ash from Iceland, an exceptionally widespread tephra layer in Europe, collected in Iceland and Norway. Using X‐ray computed tomography and optical microscopy, we show that distal ash is more anisotropic than proximate ash, suggesting that shape exerts an important control on tephra dispersion. Shape also impacts particle size measurements. Particle long axis, a parameter often reported by tephrochronologists, is on average greater than geometric size, used by dispersion modellers. By using geometric size and quantifying shape, we can explain the transport of Vedde ash particles more than 1200 km from source. We define a set of best practices for measuring the size and shape of cryptotephra shards and discuss the benefits and limitations of using physical particle properties to understand cryptotephra transport.

Comparison of lake and land tephra records from the 2015 eruption of Calbuco volcano, Chile - Keri McNamara; Alison C. Rust; Katharine V. Cashman; Angelo Castruccio; Ana M. Abarzúa (Bulletin of Volcanology, 2019)

Experimental phase equilibria of a Mount St. Helens rhyodacite: a framework for interpreting crystallization paths in degassing silicic magmas - Jenny M. Riker; Jonathan D. Blundy; Alison C. Rust; Roman E. Botcharnikov; Madeleine C. S. Humphreys (Contributions to Mineralogy and Petrology, 2015)

Petrological imaging of an active pluton beneath Cerro Uturuncu, Bolivia - Duncan D. Muir; Jon D. Blundy; Michael C. Hutchinson; Alison C. Rust (Contributions to Mineralogy and Petrology, 2014)